Ecosystem planning in Florida : solving regional problems through local decision-making - Brody, Samuel David (Aldershot, Hampshire, England ; Burlington, VT : Ashgate, 2008)
"By looking at land-use planning in Florida, this volume recognizes the need for planners and resource managers to address ecosystem problems at local and community levels." "The factors causing ecosystem decline, such as rapid urban development and habitat fragmentation occur at the local level and are generated by local land use policies. This book argues that understanding how local jurisdictions can capture and implement the principles of managing natural systems will lead to more sustainable levels of environmental planning in the future."--BOOK JACKET.
Table of contents only http://www.loc.gov/catdir/toc/fy0805/2008002623.html
Includes bibliographical references (p. [185]-202) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Ecosystem management -- Florida -- Planning; Ecosystem management -- Florida -- Decision making; Florida; Electronic books